Nitridasi Bahan Cor-Ten Untuk Meningkatkan Kekerasan dan Ketahanan Korosi Suhu Tinggi - Surian Pinem; Elman Panjaitan (JIEMS (Journal of Industrial Engineering and Management Systems), 2017)
Samples of Cor-Ten steels have been subjected to surface treatment, by coating Al and followed by nitridation. High-temperature corrosion tests were carried out using a Thermo Gravimetry Analysis / Magnetic Suspension Balance (TGA/MSB). The Nitridation process was performed at 550°C for 3, 5, 4, 7 and 20 hours under flowing N2 and NH3 gases. Corrosion tests were performed for 50 hours at 650°C. After the oxidation, sample were characterized using X-Ray Diffractometer (XRD) to determine the crystal structure, and then using Scanning Electron Microscope (SEM) to observe the microstructure and hardness of the alloys by aloowing Micro Hardness Tester. It can be concluded that sample nitridized for 5 hours showed the lowest corrosion rate or highest corrosion resistance, due to the corrosion barrier was Al2O3 protective layer. The hardness of Cor-Ten increased from 137 VHN to 340VHN (after nitridation), and to 744 VHN after Al deposition and nitridation for 5 hours. The increase of hardness might be associated with the formation of aluminum nitride.Keywords: Al Deposition, Corrosion Resistant, Cor-Ten, Nitridation, TGA/MSB, XRD, SEM